2017
DOI: 10.1123/ijspp.2015-0489
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the Nature of the Pedaling Activity on Maximal Aerobic Power in Cycling

Abstract: The results suggest that PO depends on the nature of the pedaling activity. Moreover, PO under CE TT4 is a relevant predictor of MAP. It seems important to measure MAP by taking into account the cycling conditions, considering that coaches and scientists use this parameter to assess the aerobic potential of athletes and determine the exercise intensities useful for monitoring adaptation to training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…Indeed, outdoor and indoor measures were strongly correlated. These findings are in agreement with previous studies that have reported comparable mean power output for shorter 4-min time-trials (~3% difference) (Bouillod et al 2017) and longer 40 km time trials (~3% difference) (Smith et al 2001) (> 1% difference) (Jobson et al 2008), performed indoors and outdoors. However, despite the relative consistencies in power output, a notable increase in the variability of power output during cycling performed outdoors was only recognizable with an increased level of resolution.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, outdoor and indoor measures were strongly correlated. These findings are in agreement with previous studies that have reported comparable mean power output for shorter 4-min time-trials (~3% difference) (Bouillod et al 2017) and longer 40 km time trials (~3% difference) (Smith et al 2001) (> 1% difference) (Jobson et al 2008), performed indoors and outdoors. However, despite the relative consistencies in power output, a notable increase in the variability of power output during cycling performed outdoors was only recognizable with an increased level of resolution.…”
Section: Discussionsupporting
confidence: 93%
“…When examined at increased resolution, these fluctuations may illustrate complex intrinsic control strategies to modulate work rate (Tucker et al 2006) and reflect multiple levels of regulation to achieve homeostatic control during a task (Lambert et al 2005;St Clair Gibson et al 2006;St Clair Gibson et al 2018). Given the additional external demands associated with performance cycling outdoors, it is interesting that mean power data is comparable indoors and outdoors over shorter duration 6-s sprints (Gardner et al 2007), 4-min time-trials (Bouillod et al 2017) and longer duration 40-km time-trials despite a ~ 6% reduction in performance time outdoors (Smith et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the results of the correlation matrix, which reveals that when core temperature increases, heart rate also increases. These results are in agreement with the study by Bouillod et al [68], which shows that power is greater over a similar effort (the same power output in incremental testing) when the road gradient is 8% than when it is −0.2%.…”
Section: The Elevation Gradientsupporting
confidence: 93%
“…Nevertheless, this protocol offers a situation with very low PO variation and without free wheel periods, as in natural-use scenarios. A recent study [ 21 ] showed that the variations in PO were lower with ergometer conditions (CV = 6.8%) compared to the level ground (CV = 14.5%) and uphill (CV = 14.1%) conditions for similar exercises. These results suggest that the PO fluctuations were significantly higher under road-cycling conditions by considering the different techniques, vibrations, and pacing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Power output (PO) [ 1 ] measurement during riding is an interesting method to quantify the intensity of exercise produced by cyclists or patients. This measurement is widely used in cycling during training and monitoring [ 2 , 3 , 4 , 5 , 6 , 7 ] to test or validate mathematical models [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], assess the physical potential of cyclists [ 19 , 20 , 21 , 22 , 23 , 24 ] or measure performance requirements in competitions [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. In addition, the PO measurement can be used for many research purposes to quantify the effects of rehabilitation programmes [ 32 ] or evaluate the fitness level improvement induced by medical treatments, recovery techniques, and many other approaches [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%